DEVELOPING THE MATHEMATICAL MODULE FOR CLASS VIII STUDENTS ON ALGEBRA OPERATION USING GUIDED INQUIRY - Sri Wahyuningsih; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2019)
This research was based on the teacher's rule. The facilitator task requires a teacher to provide teaching materials appropriate to the learning process. The purpose of this research was to develop products that can be used in mathematics learning. This research is a module for grade VIII students of Junior High School (SMP) on Algebraic operations using guided discovery. This research used the Research and Development (R & D) steps. The steps included two aspects: (1) planning and making module (2) propriety. Planning and making module include: (a) Potency and problems, (b) data collecting, (c) Product Design, (d) Validation of design, (e) Revision of the design. The propriety module includes: (a) The product's test and (b) its revision. The instruments used in the module are: (1) The evaluation sheet of media experts, (2) the evaluation sheet of materials experts, and (3) The sheet of student response. Validation analysis of module is 83 (very good) for media expert, 80,333 (very good) for material expert, and 73,6256 (very good) for the student's response. The instrument from media experts, material experts, and student response showed that the average was 236,9586 in the very good category. Based on the combined analysis by media experts, material experts, and student response, the module for grade VIII of Junior High School on algebraic operation using guided discovery Principles is very good and proper for use.